Treatment registry in focal epilepsy (TRIP): Multicenter observational study in Lebanon. (April 2015) - Beydoun, Ahmad; Sawaya, Marie-Thérèse; Alam, Emile; Hmaimess, Ghassan; Ezzeddine, Kamel; Younes, Fariha
Highlights: 77.6% of patients achieved a 6-month terminal seizure remission on their first AED. Those with an epileptogenic lesion had lower odds of achieving a 6-month remission. Those with focal motor seizures were significantly less likely to be seizure free. This study demonstrates the feasibility of conducting multicenter trials in Lebanon. Abstract: Purpose: Treatment of newly diagnosed epilepsy with a single antiepileptic drug (AED) is the favored approach for seizure management. This observational study aimed to assess, under daily practice conditions, remission and retention rates with the first AED prescribed as monotherapy in patients newly or recently diagnosed with focal epilepsy. Methods: The treatment registry in focal epilepsy (TRIP) study was conducted on 234 Lebanese patients with newly or recently diagnosed focal epilepsy, requiring treatment with an AED. Demographics, baseline focal seizure characteristics and results of the Clinical Global Impression (CGI) scale at the 12-month visit were reported. The primary objective of this study was to assess the percentage of patients who achieved a 6-month terminal seizure remission at the 12-month visit following treatment with a first AED administered as monotherapy. Secondary outcome variables included the calculation of the 6-month terminal seizure remission according to the baseline seizure types and patient retention at the 12 and 18 month visits. In addition, bivariate and multivariate analyses were conducted to identify independent predictors of 6-month terminal seizure remission at the 12-month visit. Results: The mean age of the 234 eligible patients was 31.6 years and the majority were males (62%). At baseline, the most common type of focal seizures was focal seizures with impairment of consciousness (45%), and the most frequent topographical localization was in the temporal lobe (47%). In total, 77.6% of the patients achieved a 6-month terminal seizure remission at the 12-month visit. Patients with an epileptogenic lesion on neuroimaging were significantly less likely to achieve a 6-month remission compared to those with no identifiable pathological substrate. Patients with focal motor seizures without impairment of consciousness at baseline had significantly lower odds of achieving a 6-month terminal seizure remission compared to patients with a combination of seizure types. There was no significant association between age or gender and 6-month terminal seizure remission. The retention rates were 95.7% and 88.5% at months 12 and 18 respectively with the great majority of patients (90.7%) reporting marked improvement on the CGI scale. Conclusions: A substantial proportion of patients with newly diagnosed epilepsy achieved a 6-month terminal seizure remission following treatment with a first AED administered as monotherapy. Patients with an epileptogenic lesion on neuroimaging and those with focal motor seizures without impairment of consciousness at baseline were significantly less likely to achieve a 6-month terminal seizure remission. This study demonstrated the feasibility of conducting long-term multicenter studies in Lebanon and will hopefully serve as an impetus to conduct randomized studies in the field of epilepsy.